(untitled) (Palíndromo, 2024)
This article examines how the art historian Aby Warburg read and appropriated the work of Friedrich Nietzsche. Although the philosopher’s name is not mentioned once in his published writings, his influence is clearly felt in the historical framework that Warburg presents in relation to the broad phenomenon of the afterlife of antiquity in the European Renaissance. To examine this topic, the article is divided into two parts. First, the development of Warburg’s research on the Renaissance is analysed, highlighting the formulation of concepts that point to a Nietzschean influence, such as the “psychology of polarity” and the “pathos formula”. The documentary collection that Warburg left behind in the form of manuscripts and letters is then analysed in order to provide fundamental elements for understanding his interpretation of the philosopher’s work.